Groundwater governance: Knowledge, motivation and agency - Ringler, Claudia; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2024)
Presentation given at Pakistan Water Week for Initiative for the CGIAR Initiative on NEXUS Gains on November 4, 2024.